Breadth of Fc-mediated effector function correlates with clinical immunity following human malaria challenge - Nkumama, Irene Nailain; Ogwang, Rodney; Odera, Dennis; Musasia, Fauzia; Mwai, Kennedy; Nyamako, Lydia; Murungi, Linda; Tuju, James; Fürle, Kristin; Rosenkranz, Micha; Kimathi, Rinter; Njuguna, Patricia; et al. (Immunity, 2024)
Malaria is a life-threatening disease of global health importance, particularly in sub-Saharan Africa. The growth inhibition assay (GIA) is routinely used to evaluate, prioritize, and quantify the efficacy of malaria blood-stage vaccine candidates but does not reliably predict either naturally acquired or vaccine-induced protection. Controlled human malaria challenge studies in semi-immune volunteers provide an unparalleled opportunity to robustly identify mechanistic correlates of protection. We leveraged this platform to undertake a head-to-head comparison of seven functional antibody assays that are relevant to immunity against the erythrocytic merozoite stage of Plasmodium falciparum. Fc-mediated effector functions were strongly associated with protection from clinical symptoms of malaria and exponential parasite multiplication, while the gold standard GIA was not. The breadth of Fc-mediated effector function discriminated clinical immunity following the challenge. These findings present a shift in the understanding of the mechanisms that underpin immunity to malaria and have important implications for vaccine development.